(untitled) (Journal of the College of Basic Education, 2022)
Since persons with disabilities and special needs are among the most vulnerable segments of societies and in most countries, it was necessary to provide protection for these persons, whether it is international protection or national protection and in various respects. The international community has taken care of these people through the development of many international instruments, starting with the Declaration of the Rights of the Mentally Retarded in 1971 and ending with the Convention on the Rights of Persons with Disabilities of 2006, and most countries have also taken care of this segment by joining these instruments, especially this Convention, and enacting laws to protect these people and this What the Iraqi legislator did by ratifying that agreement and enacting the Law of Rights and Privileges for the Disabled and People with Special Needs in the Kurdistan Region - Iraq No. 22 of 2011, and the Welfare of Persons with Disabilities and Special Needs Law No. 38 of 2013. Full legal protection for these people, and this protection was limited to access to the protection provided by international law in some cases.